Aegla manuinflata, a new species of freshwater anomuran (Decapoda: Anomura: Aeglidae) from Brazil, determined by morphological and molecular characters - Santos, Sandro; Bond-Buckup, Georgina; Pérez-Losada, Marcos; Bartholomei-Santos, Marlise Ladvocat; Buckup, Ludwig (Zootaxa, 2009)
A new species of freshwater anomuran, Aegla manuinflata n. sp. (Decapoda: Anomura: Aeglidae), is described from the Ibicuí River basin, a tributary of the Uruguay River, from the central region of the state of Rio Grande do Sul, Brazil. It can be distinguished from its congeners based on both morphological and molecular (mitochondrial gene — COII) evidence. Morphologically, the new species partly resembles A. inermis and A. uruguayana, but differs in having an inflated cheliped propodus and more elongated dactyls, besides other features. Our molecular results showed a high degree of genetic divergence between A. manuinflata and its sister group (composed of A. singularis, A. uruguayana, A. rossiana and A. platensis), an indication of species distinctness within the Aeglidae.